(untitled) (Bulletin of criminological association of Ukraine, 2024)
The content and significance of social standards as a component of the legal policy of the state is highlighted in the article using a general theoretical analysis. Based on the analysis of the provisions of the Constitution of Ukraine and current legislation on state social standards, a system of factors has been identified that indicate that the establishment of state social standards is a component of the state’s legal policy. This is, in particular, the determination by the current version of the Basic Law of Ukraine that Ukraine is a social state and the regulation of a wide list of social rights of an individual, the determination at the legislative level of the purpose of state social standards, the establishment of a broad classification of social standards by scope of application (social standards in the sphere of population income, in the sphere of providing social services, in the sphere of housing and communal services, in the sphere of transport services and communication, in the sphere of health protection, in the sphere of provision of educational services, in the sphere of service by cultural, physical culture and sports institutions, in the sphere of household services , trade and catering). The position that the legislative definition of social standards within the legal policy of the state contributes to qualitative changes in social relations is proven. In particular, - the necessary minimum legal order is established, which minimizes the risks of a negative social situation, and a specific person is protected from the primary negative effects of living conditions. The prospective direction of improving the legal policy of the state in terms of determining state social standards is outlined, which consists in the further introduction of legal innovations and norms into the legal system, which would strengthen the social guarantees of all sections of the population at the regulatory level.